Autonomous agriculture monitoring system for climate-soil parameters - Minin, I. N.; Badin, Alexander V.; Sitnikov, S. A.; Perevalov, A. V.; Yuzhakov, Mikhail S. (Russian physics journal)
The paper studies autonomous monitoring systems for climate-soil parameters equipped with humidity sensors, atmospheric pressure sensors, air/soil temperature sensors, and carbon dioxide sensors. The hard- and software are proposed in this work. The operating principle of the monitoring system is described herein. Research results concern the dynamics of soil temperature changes in agricultural fields